E-PROCUREMENT SYSTEM PENGADAAN BARANG DAN JASA PADA PT. TRAKINDO UTAMA SURABAYA - Utama, A.A Gde Satia; Prabiyanto, Arief Eko (Universitas Airlangga, 2019)
The aim of this study proposes new system for PT Trakindo asan officialagent company (dealer) in Indonesia for Caterpillar products. The company's operations are the world's largest heavy equipment manufacturer which includes miningindustry, oil and gas industry, construction, forestry, agriculture, and power systems. The problem is Procurement of goods and services performed by PT Trakindo Utama currently undergoing a lot of obstacles such as significant cost in finding the right suppliers, bad integration with suppliers, dependence on suppliers, the bill submitted by the supplier can not timely because the billing document incomplete, the use of media such as telephone and so on which may cause considerable cost.The contribution of this research are developing the procurement system design, and web-based services are expected to help anticipate and resolve these problems. This research was conducted using qualitative and case study method, which has the characteristics of exploratory. The results achieved are expected to improve the efficiency and effectiveness of the procurement process at PT Trakindo Utama.